Function in unaffected arms of children with obstetric brachial plexus palsy - KARADAĞ SAYGI, NAİME EVRİM; KENİŞ COŞKUN, ÖZGE (W.B. Saunders Ltd, 2018)
Objective: The objective is to compare the fine and gross motor function of unaffected arms of children with obstetric brachial plexus palsy (OBBP) with typically developing children's dominant upper extremities. Methods: Fifty-three patients with OBBP and fifty-one typically developing children between the age of 4 and 13 were included in the study. For gross motor function evaluation in the upper extremity box-block test (BBT), for fine motor skill nine-hole peg (9HP) test was used. For grasp and pinch strength measurements, a Jamar dynamometer is used. Results: The patient group performed significantly worse in 9HP and BBT tests. When further divided into age groups, 4–8 age patient group performed significantly worse in 9HP and BBT tests, while there were no differences in children in the 9–13 age group. Conclusions: The fine and gross motor functions of the unaffected arms of children with OBPP are significantly worse in children between the ages of four and eight but this deficit improves with age, and possibly with ongoing therapy. © 2018 European Paediatric Neurology Society
Keywords: Brachial plexus; Obstetric brachial plexus palsy; Pediatric rehabilitation; Rehabilitation